Associations of specific types of sports and exercise with all-cause and cardiovascular-disease mortality: a cohort study of 80 306 British adults. Issue 10 (28th November 2016) - Oja, Pekka; Kelly, Paul; Pedisic, Zeljko; Titze, Sylvia; Bauman, Adrian; Foster, Charlie; Hamer, Mark; Hillsdon, Melvyn; Stamatakis, Emmanuel
Abstract : Background/Aim: Evidence for the long-term health effects of specific sport disciplines is scarce. Therefore, we examined the associations of six different types of sport/exercise with all-cause and cardiovascular disease (CVD) mortality risk in a large pooled Scottish and English population-based cohort. Methods: Cox proportional hazards regression was used to investigate the associations between each exposure and all-cause and CVD mortality with adjustment for potential confounders in 80 306 individuals (54% women; mean±SD age: 52±14 years). Results: Significant reductions in all-cause mortality were observed for participation in cycling (HR=0.85, 95% CI 0.76 to 0.95), swimming (HR=0.72, 95% CI 0.65 to 0.80), racquet sports (HR=0.53, 95% CI 0.40 to 0.69) and aerobics (HR=0.73, 95% CI 0.63 to 0.85). No significant associations were found for participation in football and running. A significant reduction in CVD mortality was observed for participation in swimming (HR=0.59, 95% CI 0.46 to 0.75), racquet sports (HR=0.44, 95% CI 0.24 to 0.83) and aerobics (HR=0.64, 95% CI 0.45 to 0.92), but there were no significant associations for cycling, running and football. Variable dose–response patterns between the exposure and the outcomes were found across the sport disciplines. Conclusions: These findings demonstrate that participation in specific sports may have significant benefits for public health. Future research should aim to further strengthen the sport-specific epidemiological evidence base and understanding of how to promote greater sports participation.